Underuse of brachytherapy for the treatment of dysphagia owing to esophageal cancer. An Italian survey. Issue 10 (October 2016) - Fuccio, Lorenzo; Guido, Alessandra; Hassan, Cesare; Frazzoni, Leonardo; Arcelli, Alessandra; Farioli, Andrea; Giaccherini, Lucia; Galuppi, Andrea; Mandolesi, Daniele; Cellini, Francesco; Mantello, Giovanna; Macchia, Gabriella; et al.
Abstract: Background: International guidelines strongly recommend brachytherapy as valid alternative or in addition to stenting in patients with dysphagia owing to esophageal cancer. However, for not well understood reasons, brachytherapy is definitively underused for the palliative treatment of malignant dysphagia. Aim of the current survey was to investigate the use of brachytherapy for the treatment of malignant dysphagia in Italy. Methods: A structured questionnaire was submitted to the 1510 members of the Italian Association of Radiation Oncologists (AIRO). These members refer to 177 centres of radiotherapy across Italy and in 68 (38.4%) of them brachytherapy is routinely performed. Results: Of the 1510 invited members, 178 completed the survey (11.7%). The answers provided by the 178 participants allowed to get information on 40 out of 68 brachytherapy centres (58.8%). Seven out of 40 (17.5%) centres perform brachytherapy of the oesophagus, in 3 out of 40 (7.5%) centres brachytherapy represents the first line of treatment. The main reason why brachytherapy is not routinely performed is the lack of experience. Conclusion: Despite the strong recommendations of the international guidelines and the wide diffusion of brachytherapy centres across Italy, only very few of them routinely considered brachytherapy for the treatment of dysphagia due to esophageal cancer.